Human Activity Monitoring and Recognition of Elderly People with Mild Cognitive Decline - Selvi S, Arul; M S, Sruthi; M, Madhangiri (International Journal of Engineering and Technology, 2018)
Elderly people suffering from Dementia and Alzheimer meet with a progressive cognitive decline. This make them experience hardship in performing their everyday conventional activities especially in their outdoor navigation as they tend to forget landmarks even in familiar environments due to gradual decline in their memory and thinking abilities. Hence, disorientation and wandering become common issue. Providing assistive guidance to the elderly people in their outdoor mobility has become a challenging task for caretakers and family members as most of the elders prefer to live independently. Thus, there arises a need for efficient solutions that can monitor the elderly people movements and notify the caretakers in the event of disorientation or wandering being detected. The main objective of this paper is to propose one such solution which can support the provision of the best monitoring care in the outdoor navigation by mining through the elderâ€™s historical movement trajectories and detecting outliers if any, in the elderâ€™s current on-going trajectory. Further, the system tries to identify the underlying wandering pattern such as lapping, pacing or random in the outlier that could possibly help in analyzing the effect of medication in the treatment of dementia.Â Â